PENGARUH INVESTASI TERHADAP TINGKAT PENGANGGURAN DI KABUPATEN ACEH UTARA - Muhammad Rasyidin; Cut Putri Mellita Sari; Miswar Miswar (LPPM STIE Lhokseumawe, 2017)
This study aims to determine the effect of Investments Against Unemployment in North Aceh district. Data used in this study according to the source is a time series data (time series) that is data arranged chronologically according to the time on a variable data in this study in the form of annual data for 12 years (2003-2014). From the regression equation, know that the correlation coefficient (R) = 0.925 which shows that the degree of relationship (correlation) between the independent variables (Investments) and the dependent variable (unemployment) have a relationship (correlation) is very strong. Known coefficient of determination (R2) of = 0.856 or 85.6%. This means the dependent variable (investment) can be influenced by 85.6% and the rest influenced by other factors not included in this study. From the results of the determination (R2) or Investment Effect Against Unemployment In North Aceh regency relatively strong. Variable Investment (X) of the Unemployment (Y) has a value of 7.715 while table 2.22814. The calculation results show that t count> t table with a significance level of 0.00 or in other words, testing this hypothesis accept and reject Hi Ho. This means that the variable Investment (X) significantly affect unemployment (Y).